Can Open Hand Injuries Wait for Their Surgery in a Tertiary Hospital? - Sim, Wei Ping; Ng, Hannah Jia Hui; Liang, Benjamin Zhiren; Rajaratnam, Vaikunthan (Journal of Hand and Microsurgery, 2021)
Objective Open hand injuries are routinely admitted and planned for surgery acutely, competing with other surgical emergencies. This retrospective study aims to evaluate if a delay in timing to surgery for open hand injuries led to an increased rate of infection.Materials and Methods All patients who sustained open hand injuries and underwent semi-emergent day surgery from January 1, 2015 to December 31, 2016 were included. Outcome of postoperative infection was analyzed against demographic data, injury details, and delay from trauma to therapy.Results There were 232 cases (91% males) included, with 92.0% performed under local anesthesia. Deep seated postoperative infection was seen in 1.3%, which was not significantly associated with delay to surgery.Conclusion We had comparable infection rates as compared with published literature. Delayed timing of surgical treatment in open hand injuries was not associated with increased rates of deep-seated infection. Managing open hand injuries as semi-emergent surgeries may be acceptable given the low infection rates.
Keywords: open injuries; hand injuries; infection; deep infection; semi-emergent surgery